Answer: m^10
===============================================
Step-by-step explanation:
I'm assuming you meant to write m^2 * m^5 * m^3
If so, you add the exponents to get 2+5+3 = 10 which is the exponent over the original base m. The base does not change.
The rule I used is a^b*a^c = a^(b+c). We see that the base stays the same at 'a' the whole time.
-----------
A longer way to do this is to expand out m^2 into m*m. We have two copies of m multiplied together.
Similarly, m^5 = m*m*m*m*m. We have five copies now.
Saying m^2*m^5 will have seven copies because
m^2*m^5 = (m*m) times (m*m*m*m*m) = m*m*m*m*m*m*m = m^7
Tacking on m^3 will add on three more copies of m to multiply out, giving 10 copies of m total to multiply. This alternative method is not advised since there is a possibility to lose track and make an error somewhere. The formula in the previous section is preferred. Though I recommend you try this second method out to see how/why the formula works.